2018
DOI: 10.7752/jpes.2018.04363
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Problem statement: Teaching self-efficacy is built from teacher's interpretations about and also from the personal values that he attributes to the information selected from the environment. Despite research has investigated the contributions of the sources of self-efficacy, little is known about which experiences are selected and weighted by Physical Education beginning teachers to compose teacher' self-efficacy. Purpose: This study aimed to identify, describe and analyze the learning experiences to teach tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…mentoring within the school environment or in-service training courses) (e.g. Costa Filho & Iaochite, 2018) and informal support (i.e. school with supportive and nurturing colleagues and/or principal) (Blankenship & Coleman, 2009) reported in the studies are experienced by PE teachers as useful (MacPhail & Hartley, 2016), although whether or not such support is considered adequate by new graduates depends on who provides it (Napper-Owen & Phillips, 1995).…”
Section: Balance the Rolesmentioning
confidence: 99%
“…mentoring within the school environment or in-service training courses) (e.g. Costa Filho & Iaochite, 2018) and informal support (i.e. school with supportive and nurturing colleagues and/or principal) (Blankenship & Coleman, 2009) reported in the studies are experienced by PE teachers as useful (MacPhail & Hartley, 2016), although whether or not such support is considered adequate by new graduates depends on who provides it (Napper-Owen & Phillips, 1995).…”
Section: Balance the Rolesmentioning
confidence: 99%
“…In addition, research on teacher self-efficacy and supervision revealed that teacher self-efficacy is strongly associated with the evaluation of teachers' effectiveness during the supervision process by their colleagues, supervisors, or administrators (Klassen ve Tze 2014;McDonnough & Matkins, 2010). A limited number of studies in the field of physical education have also revealed that the knowledge and skills acquired by pre-service teachers, especially during the controlled supervision process in authentic school practice, contribute positively to their self-efficacy perception level (Costa Filho & Iaochite, 2018;Gurvitch & Metzler, 2009). In the case of physical education teacher candidates, revealing their self-efficacy beliefs and views on supervision at an early stage of career development may help with learning about future teaching behaviors and taking preventative measures against potential negative outcomes (Schnitzius et al, 2021).…”
Section: Introductionmentioning
confidence: 99%